(untitled) (Yangi O’zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2023)
It wasn’t long after the birth of experimental phonetics that people became increasingly interested in the physical qualities of speech sounds. The experimental methodology makes it possible to describe in detail the qualities of the mechanisms that are responsible for the production of sound in a complete manner. During the latter half of the nineteenth century, Kazan University was the site of the world’s first experimental phonetics investigations, which took place there as well. It was already recognised as significant at the time, and as a result of this recognition, it became possible to substantiate the theory and methodology of experimental study of the sound structure of the language in a creative and methodologically correct manner, as well as to predict milestones and steps for future research. In addition to linguistic ideas, a large number of extralinguistic perspectives were transmitted principally through phonetic structures and units. The fact that the sounds of local speech implicitly serve as a technique of formalising mental spaces in the context of multilingualism makes it absolutely essential to investigate and discover the role of phonetics in the building of a scientific knowledge system (according to the tradition of Kazan Linguistic School, this can be a model of the word phonemography).